Never Overlook Security Awareness on Deployment - Sadewa, Rizki; Lubis, Muharman; Nuryatno, Edi Triono (Acceleration, Quantum, Information Technology and Algorithm Journal, 2024)
Since preliminary evidence supports the association between security culture and information security awareness (ISA), more research is needed to determine how it interacts with organizational culture. Beyond variations in respondent nation or gender, the study's findings also demonstrate an association between stronger cyber expertise and level of cyber awareness. Additionally, awareness is linked to defense mechanisms but not the information they were willing to divulge.  People play an even more important role in the collaboration between those teams and the security team when security is incorporated into DevOps practices. Furthermore, security is crucial when creating essential systems since it allows us to control objectives, risks, and evidence. Labor only starts after implementing security into the DevOps toolchain. To establish a security culture, we are additionally required to start with behavioral alterations. One of the largest Sharia banks in Indonesia anticipated cyberattacks in 2023, demonstrating to us how crucial security is in the modern world. Although no one could claim that using one of the security solutions would guarantee absolute safety, information security technology is quite dynamic. Future studies could improve on the current findings by taking into account national culture. This study has the aim of proving that we are never satisfied by current security maturity even if you or your company is implementing the best security tools, because the vulnerability can come from that deployment and wherever the environment itself.